2016
DOI: 10.1111/cas.12939
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic changes from pancreatic intraepithelial neoplasia to pancreatic ductal adenocarcinoma in tissues from rats

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant tumors and is difficult to diagnose in the early phase. This study was aimed at obtaining the metabolic profiles and characteristic metabolites of pancreatic intraepithelial neoplasia (PanIN) and PDAC tissues from Sprague–Dawley (SD) rats to establish metabonomic methods used in the early diagnosis of PDAC. In the present study, the animal models were established by embedding 7,12‐dimethylbenzanthracene (DMBA) in the pancreas of SD rats to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
(69 reference statements)
1
15
1
Order By: Relevance
“…This process also maintains higher reduced glutathione levels and redox balance 13 15. In previous metabolomic studies, blood, saliva and tumour tissue glutamate concentrations have been associated with PDAC in small case-control studies,16–19 and rodent studies have shown higher glutamate concentrations in blood and pancreatic tissue from pancreatic intraepithelial neoplasia and PDAC compared with control animals 20 21. These studies show less consistent associations for aspartate 21 22…”
Section: Discussionmentioning
confidence: 99%
“…This process also maintains higher reduced glutathione levels and redox balance 13 15. In previous metabolomic studies, blood, saliva and tumour tissue glutamate concentrations have been associated with PDAC in small case-control studies,16–19 and rodent studies have shown higher glutamate concentrations in blood and pancreatic tissue from pancreatic intraepithelial neoplasia and PDAC compared with control animals 20 21. These studies show less consistent associations for aspartate 21 22…”
Section: Discussionmentioning
confidence: 99%
“…112,113 Investigations of pancreatic cancer using animal models have been made based on metabolite profiling of tissue extract and serum. 114,115 The disease model included both pancreatic intraepithelial neoplasia and pancreatic ductal adenocarcinoma and the results showed significant differences in metabolite profiles between the two pathological conditions. In the area of ovarian cancer, ovarian cyst fluid samples from benign, borderline, and malignant ovarian tumors were investigated.…”
Section: Applicationsmentioning
confidence: 99%
“…Metabolomics, a noninvasive diagnostic technology that focuses on the metabolite profiles involved in disease perturbations and provides a characteristic fingerprint in disease, has been applied to clinical studies of many diseases, including different cancers . It is regarded to be a sensitive, accurate and high‐throughput platform for cancer diagnosis, prognostic evaluation and clinical trials, and ultra‐high performance liquid chromatography quadrupole time‐of‐flight mass spectrometry (UPLC‐Q‐TOF/MS) technology has been widely used for metabolite profiling in various clinical samples (eg, in serum and urine).…”
Section: Introductionmentioning
confidence: 99%